FORENSIC ACCOUNTING AS A TOOL FOR FRAUD PREVENTION: A LITERATURE REVIEW IN THE INDONESIAN CONTEXT - Linatul Uyun (Count : Journal of Accounting, Business and Management, 2025)
This study aims to explore the role of forensic accounting as a fraud prevention tool in the Indonesian context through a systematic literature review. As financial crimes become increasingly complex—especially in emerging economies like Indonesia—the application of forensic accounting is gaining relevance, yet remains underutilized. This research adopts a qualitative approach using secondary data from peer-reviewed journals, government reports, and professional publications published between 2010 and 2024. The data were analyzed through thematic content analysis to identify key issues, research gaps, and best practices. The findings show that forensic accounting in Indonesia is still at a developmental stage, hindered by regulatory ambiguity, lack of certified professionals, and limited integration with digital forensic tools. Educational infrastructure also lags behind global standards, contributing to a mismatch between academic training and market demands. A key novelty of this study lies in its contextualized synthesis, which not only examines the technical aspects of forensic accounting but also addresses institutional, educational, and cultural factors specific to Indonesia. Additionally, this research bridges forensic accounting with technological developments, advocating for the integration of data analytics and cybersecurity in audit practices. The study concludes that a holistic reform encompassing education, legal frameworks, and technological infrastructure is essential to maximize the impact of forensic accounting in curbing fraud. This paper serves as a reference point for policymakers, academics, and practitioners seeking to enhance financial transparency and accountability in emerging markets.